DETERMINANTS OF DIVIDEND POLICY AND ITS IMPLICATIONS FOR STOCK RETURNS: AN EMPIRICAL STUDY OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2019-2024 - Baliyah Munadjat; Hari Gursida; Yohanes Indrayono (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the determinants of dividend policy and their implications for stock returns among companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Specifically, the study examines the effects of Return on Assets (ROA), Current Ratio (CR), Debt-to-Equity Ratio (DER), Sales Growth (SG), and Firm Size (SIZE) on Dividend Payout Ratio (DPR), as well as the impact of DPR on stock returns. The research employs a quantitative approach using secondary data obtained from the annual financial reports of dividend-paying companies listed on the IDX. The sample consists of 822 firm-year observations selected through purposive sampling. Data analysis was conducted using path analysis with multiple regression models, supported by classical assumption tests including normality, heteroscedasticity, multicollinearity, and autocorrelation tests. The results indicate that during the overall period of 2019–2024, ROA, DER, and SG significantly and negatively affect DPR, while CR and SIZE do not have significant effects. Furthermore, CR negatively affects stock returns, whereas SG and DPR have positive and significant effects on stock returns. The findings also reveal that the relationships among financial performance, dividend policy, and stock returns vary across pre-crisis, crisis, and post-crisis periods. Overall, dividend policy plays an important mediating role in influencing stock returns, particularly during and after periods of financial uncertainty. These findings provide valuable insights for investors, corporate managers, and policymakers in formulating dividend and investment decisions under different economic conditions.